Ethno-scientific teaching approach, student proficiency and attitude toward science and ethnic culture - Hiwatig, April Daphne Floresca (Education quarterly.)
This study aimed to determine the effect of ethno-scientific teaching approach on first year high school students' learning in science. Such approach was applied to a class of 40 students while the conventional teaching approach was used in another class of 40 students. The results indicated that students from ethno-scientific and conventional teaching groups did not differ in their performance in science proficiency test. It was found that the students' attitude towards science, ethnic culture, and their proficiency in science were significantly and positively correlated. This study is intended to make teaching in multicultural communities more effective and meaningful.